Study of Pyramids with Equal Edges, Which Have Equal Radius of the Circle Described Around Their Base - Toni Chehlarova; Neda Chehlarova (Педагогически форум)
Computer models for studies with pyramids with equal edges whose bases are inscribed in a specific circle are presented. Ideas for modifying some of them are discussed, with a view to improving the results. The computer models were developed with the dynamic software GeoGebra. Files for creating 3D printed models are also provided. The use of these resources for learning the software is commented.